If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17 + 13 + 18s = 18 + 16s Combine like terms: -17 + 13 = -4 -4 + 18s = 18 + 16s Solving -4 + 18s = 18 + 16s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-16s' to each side of the equation. -4 + 18s + -16s = 18 + 16s + -16s Combine like terms: 18s + -16s = 2s -4 + 2s = 18 + 16s + -16s Combine like terms: 16s + -16s = 0 -4 + 2s = 18 + 0 -4 + 2s = 18 Add '4' to each side of the equation. -4 + 4 + 2s = 18 + 4 Combine like terms: -4 + 4 = 0 0 + 2s = 18 + 4 2s = 18 + 4 Combine like terms: 18 + 4 = 22 2s = 22 Divide each side by '2'. s = 11 Simplifying s = 11
| -5x+8=-2x-7 | | x+23+2x=-5-2x-12 | | x+4547=14165 | | 5x(3+2x)-x(10x+1)=8x+12 | | 4547-x=14165 | | 9y^2=10 | | 2x+15=-9 | | 4t+7-t=2t-3 | | -a(-a)3=180 | | -8n+4(1+5n)=-6n-14n | | -13-12x=11-10x | | -x+9=2x+30 | | 7h-6=8-7h | | -2x+15=45-8x | | 22x+4=14x+28 | | -2x-3=x-15 | | -80.1+n=-86 | | 12x-3+105=180 | | 5+x/4=12 | | 10(x+2)=-80 | | 18-3x=3x | | ab-3a+2b-6= | | -4(x+2)-41=3-16 | | 10(x-9)=-80 | | 8x-7=4x+3 | | 8(x)(x)+40x= | | 8+6/-4-3=-10 | | 21x+8-24x=1-8 | | 21x+8-24x=1-7 | | -20=k+15-8k | | -20=k | | 25x+6-27x=5-7 |